PENGARUHPERPUTARAN MODAL KERJA TERHADAP KINERJA KEUANGAN CV. PUTRA BUANA PALEMBANG - Desfitrina Desfitrina (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this research is to know how to influence working capital turnover againts financial performance at CV. Putra Buana years 2009-2014. While the research method used is descriptive with simple linear regression.Working capital management is very important because it concerns of working capital as well as the working capital policy implementation in day to day operations, and short term liabilities the company so that the continuity of the company’s future can be maintained. The management of working capital effect on the ability of the company in generating profits. From the data obtained, the financial condition of the CV. Putra Buana years 2009-2014 tends to still fluctuate. To improve the financial performance of CV. Putra Buana required increased efficiency and profit margin turnover assets, because the end result of the mixture of both efficiency and profit margin turnover assets (operating assets turnover) specifies the height of the low earning power.